Witnesses to freedom young people who fought for civil rights - Rochelle, Belinda (New York : Puffin Books, 1997)
Describes the experiences of young Blacks who were involved in significant events in the civil rights movement, including Brown vs. Board of Education, the Montgomery bus boycott, and the sit-in movement.
1040L
Keywords: African Americans -- Civil rights; Civil rights workers -- United States; African Americans; Civil rights movements -- United States -- History -- 20th century